Cardiovascular imagingSlow-flow phenomenon after elective percutaneous coronary intervention of computed tomography-detected vulnerable coronary lesion - Wolny, Rafał; Dębski, Artur; Kruk, Mariusz; Kępka, Cezary (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
No-reflow or slow-flow phenomenon is one of the serious complications of percutaneous coronary interventions (PCI) in acute myocardial infarction, as well as during elective procedures, and is an independent predictor of myocardial infarction, and in-hospital and long-term mortality. We present a case of an elective PCI of native coronary artery lesion that was assessed to be vulnerable based on coronary computed tomography angiography, complicated with slow-flow phenomenon.